Mustafa Shokay and Turkic unity and independence (Herald of Journalism, 2020)
In the article the tie between Mustafa Shokay and unity and indepen- dence of the Turkic countries is considered. The various dynamic person- ality of Mustafa Shokay who devoted and risked the life for the sake of interest and purpose of the nation was disclosed. In the article an attempt to define a role of huge works of Mustafa Shokay which are manual, moral incentive of life for generation of the Independent Turkic countries is made.
Keywords: Mustafa Shokay, the Turkic world, the party of Alash, uni- ty, politics.